2020
DOI: 10.1055/a-1165-0169
|View full text |Cite
|
Sign up to set email alerts
|

Modified Kudo classification can improve accuracy of virtual chromoendoscopy with FICE in endoscopic surveillance of ulcerative colitis

Abstract: Background and study aims Virtual chromoendoscopy with Fuji Intelligent Color Enhancement (FICE) has never been studied in prospective trials of endoscopic surveillance for ulcerative colitis (UC). We compared FICE and white light endoscopy (WLE) in differentiation of visible lesions in UC. Patients and methods In a prospective parallel study, we compared consecutive outpatients with UC submitted to surveillance colonoscopy with FICE or WLE. At least one visible polypoid or non-polypoid lesion for ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…Twenty-four studies reported the use of Kudo classification for lesion characterization in IBD (predominantly patients with UC). 6,7,1216,20,22,23,28,31,3338,4042,4446 Eighteen studies used DCE (IC: 13, MB: 5, CV: 6), whereas 11 studies used VCE (NBI: 7, FICE: 2, i-SCAN: 2); magnification was used in 17 studies, and HD in 19 studies (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-four studies reported the use of Kudo classification for lesion characterization in IBD (predominantly patients with UC). 6,7,1216,20,22,23,28,31,3338,4042,4446 Eighteen studies used DCE (IC: 13, MB: 5, CV: 6), whereas 11 studies used VCE (NBI: 7, FICE: 2, i-SCAN: 2); magnification was used in 17 studies, and HD in 19 studies (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In all studies, Kudo pit patterns III–V were considered suspicious for neoplasia, whereas Kudo pit patterns I–II were combined and considered non-neoplastic as previously described in the non-IBD literature. 55 When the frequency of these groups of pit patterns was clearly reported (2296 lesions – 19% neoplastic, from 13 studies; Table 2), 6,7,12,13,15,16,20,22,23,28,34,40,42 most lesions (65%) had non-neoplastic type I–II pits, whereas 26% were suspicious for neoplasia (Kudo III–V patterns). However, when the Kudo patterns were compared to histology (1645 lesions from 12 studies clearly reporting the rates of true and false positives/negatives), 6,7,12,13,15,16,20,22,23,28,40,42 4% of Kudo I–II patterns were neoplastic, whereas only 44% of Kudo III–V were neoplastic.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies conducted by the same research group reported the usefulness of FICE for differentiating neoplasia from non-neoplasia. 25,40 Their recently modified Kudo's pit pattern under FICE for adaptation to lesions in patients with UC and prospective evaluation of the new classification, which they termed FICE-KUDO/inflammatory bowel disease (IBD), showed a sensitivity of 93% and specificity of 97% in comparison with those of white light endoscopy (86% and 64%, respectively). 40 Iacucci et al 38 developed a multimodal classification (including CE, NBI, and i-scan OE) for optical diagnosis of IBD-associated neoplasia using advanced endoscopic imaging.…”
Section: Digital Cementioning
confidence: 99%
“…25,40 Their recently modified Kudo's pit pattern under FICE for adaptation to lesions in patients with UC and prospective evaluation of the new classification, which they termed FICE-KUDO/inflammatory bowel disease (IBD), showed a sensitivity of 93% and specificity of 97% in comparison with those of white light endoscopy (86% and 64%, respectively). 40 Iacucci et al 38 developed a multimodal classification (including CE, NBI, and i-scan OE) for optical diagnosis of IBD-associated neoplasia using advanced endoscopic imaging. The classification consisted of four criteria: morphology, surface architecture, vessel architecture, and inflammation within the lesion (Fig.…”
Section: Digital Cementioning
confidence: 99%
“…Alternatively, random quadrant biopsies every 10 cm and targeted biopsies of any visible lesion should be performed if conventional, and not if HD-WLE is used. The combination of virtual CE with targeted biopsies is superior to a combination of white light endoscopy with random biopsies [110]. With regard to the increased tumor risk, additional random quadrant biopsies should always be taken every 10 cm in PSC patients [2].…”
Section: What To Tell Patients With Regard To Covid19 and Vaccination...mentioning
confidence: 99%